2000
DOI: 10.1111/j.1365-2141.2000.02473.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation increases shear stress‐induced platelet plug formation measured by the PFA‐100

Abstract: Summary. The PFA-100 measures platelet plug formation under shear stress and is strongly dependent on von Willebrand Factor (VWF) levels in plasma. We therefore hypothesized that elevated VWF levels, possibly as a result of acute inflammation, adversely influence PFA-100 results. Healthy volunteers received either 2 ng/kg endotoxin or placebo in a randomized controlled trial. Four hours after endotoxin (but not placebo) infusion VWF levels increased by 85%, collagen epinephrine-induced closure time (CT) decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 10 publications
9
18
1
1
Order By: Relevance
“…As previously published [26][27][28], peak VWF levels inversely correlated with nadir values of CEPI-CT (r ¼ )0.56, P < 0.05).…”
Section: Effect Of Endotoxin On Rotemsupporting
confidence: 83%
See 3 more Smart Citations
“…As previously published [26][27][28], peak VWF levels inversely correlated with nadir values of CEPI-CT (r ¼ )0.56, P < 0.05).…”
Section: Effect Of Endotoxin On Rotemsupporting
confidence: 83%
“…There was neither a change in the time course nor compared with placebo. These results are in contrast to the effects of endotoxemia on the closure time measured with the PFA-100 device [26]. LPS-infusion significantly decreased CEPI-closure time by approximately 50% to reach minimum levels after 4 h [80 s (95%CI 73-88)]; P < 0.05 vs. baseline and placebo).…”
Section: Effect Of Endotoxin On Rotemcontrasting
confidence: 61%
See 2 more Smart Citations
“…6,9 One possible reason for marked thrombocytopenia and decreased PCT in response to endotoxin may be that endotoxin induces platelet adhesion and aggregation by increasing the release of various platelet agonists and by stimulating the expression of adhesion molecules on endothelial cells. 1,15,16 Increased rolling and adherence of platelets within liver sinusoids during endotoxemia has been demonstrated, 15 and we previously showed that platelet closure times were shortened in dogs 1 hour after intravenous endotoxin injection. 6,9 Moreover, decreased survival of circulating platelets and increased removal of platelets from circulation due to phagocytosis by the liver macrophages, as described in a rat model, might enhance the severity of thrombocytopenia in dogs with endotoxemia.…”
Section: Discussionmentioning
confidence: 96%